Pengaruh Ukuran Perusahaan, Kebijakan Deviden, dan Laverage terhadap Nilai Perusahaan pada Perusahaan Manufaktur: Studi Kasus Perusahaan Manufaktu BEI 2016-2020 - Gendro Wiyono; Ratih Kusumawardhani; Desriani Lende (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Company value is very important, because high company value will be followed by high shareholder prosperity. The higher the stock price, the higher the value of the company. High corporate value is the desire of the owner of the company, because a high value indicates the prosperity of shareholders is also high. This study aims to examine the effect of firm size, leverage, and dividend policy on the value of food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study were 19 companies. In this study, firm size is proxied by firm size = Ln (Total Assets), dividend policy is proxied by DPR (dividend payout ratio), and leverage is proxied by DER (Debt To Equity Ratio). Purposive sampling method is the method used to determine the sample of this study. The analytical method used is descriptive test, classical assumption test, and multiple regression analysis test using SPSS application. The results of this study indicate that the independent variables, namely firm size, dividend policy, and leverage have a positive and significant effect on the dependent variable, namely firm value. Keywords : Company Size, Dividend Policy, Leverage, Firm Value